2002
DOI: 10.1001/archpsyc.59.11.1039
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and the Risk of Major Depressive Disorder, Alcohol Dependence, and Substance Use Disorders

Abstract: Our results suggest that early drug use is associated with and predicts later psychiatric disorders. Preventive implications stem from the importance of studying a range of psychiatric disorders in the context of substance use assessed over a wide age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
327
3
19

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(372 citation statements)
references
References 40 publications
23
327
3
19
Order By: Relevance
“…A sib-pair study showed that the personality construct 'reward dependence' has trait-like characteristics related to the familiality of major depression (Farmer et al, 2003). Given the extensive evidence for associations between impairments of brain reward pathways and addiction (Nestler et al, 2002), familial coaggregation and lifetime comorbidity of substance use disorders and MDD (Kendler et al, 1997;Brook et al, 2002) also suggest persistent familial abnormalities of brain reward pathways in MDD.…”
Section: Anhedonia (Impaired Reward Function)mentioning
confidence: 99%
“…A sib-pair study showed that the personality construct 'reward dependence' has trait-like characteristics related to the familiality of major depression (Farmer et al, 2003). Given the extensive evidence for associations between impairments of brain reward pathways and addiction (Nestler et al, 2002), familial coaggregation and lifetime comorbidity of substance use disorders and MDD (Kendler et al, 1997;Brook et al, 2002) also suggest persistent familial abnormalities of brain reward pathways in MDD.…”
Section: Anhedonia (Impaired Reward Function)mentioning
confidence: 99%
“…Other studies found illicit drug use in youth to be associated with poorer psychosocial functioning, including externalizing and internalizing symptoms (D"Amico et al, 2008;Fergusson et al, 2002). Earlier onset of drug use is particularly predictive of long-term impairments (Brook et al, 2002;Horwood et al, 2010). However, findings from prospective studies have not been completely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…When broken down by each time frame, however, they found that tobacco use prior to the early 20s (adolescence and earlier) predicted major depression in the late 20s, while tobacco use in the early 20s did not predict major depression in the late 20s. 25 They also found that tobacco use in late adolescence predicted major depression in the early 20s. 21 They concluded that these findings may suggest that there is a critical period for the adverse influence of tobacco use on later major depressive disorders.…”
Section: Introductionmentioning
confidence: 97%
“…19 Researchers found that most of the studies found positive associations between smoking and depression in adjusted or unadjusted analysis, 13,14,[20][21][22][23][24][25] while there was also some evidence for not finding cumulative frequency of early tobacco smoking related to later mental illness after adjusting for confounding factors or inconclusive results. 25,26 The evidence for whether cigarette smoking is a precursor of later depression as detected using data from longitudinal studies remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation